2021
DOI: 10.1177/03331024211047454
|View full text |Cite
|
Sign up to set email alerts
|

TOP-PRO study: A randomized double-blind controlled trial of topiramate versus propranolol for prevention of chronic migraine

Abstract: Objective The aim of the TOP-PRO-study, a double-blind randomized controlled trial, was to assess the efficacy (non-inferiority) and tolerability of propranolol compared to topiramate for the prevention of chronic migraine. Background Except for topiramate, oral preventive treatment for chronic migraine lacks credible evidence. Methods Chronic migraine patients aged above 18 years and less than 65 years of age, not on any preventive treatment were randomly allocated to receive topiramate (100 mg/day) or propra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…In the direct comparison between topiramate versus other preventive drugs, the evidence is limited. A parallel group, randomized, double-blind controlled study, conducted between May 2019 and February 2021 compared the change in migraine days per 28 weeks at the end of a 24 weeks treatment period in chronic migraine patients treated with topiramate 100 mg/day ( n = 46) or propranolol ( n = 49) [ 46 ]. The reduction in migraine days per month was -5.3 ± 1.2 days within patients treated with topiramate, and − 7.3 ± 1.1 days within patients treated with propranolol, albeit differences were not statistically significant [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the direct comparison between topiramate versus other preventive drugs, the evidence is limited. A parallel group, randomized, double-blind controlled study, conducted between May 2019 and February 2021 compared the change in migraine days per 28 weeks at the end of a 24 weeks treatment period in chronic migraine patients treated with topiramate 100 mg/day ( n = 46) or propranolol ( n = 49) [ 46 ]. The reduction in migraine days per month was -5.3 ± 1.2 days within patients treated with topiramate, and − 7.3 ± 1.1 days within patients treated with propranolol, albeit differences were not statistically significant [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A parallel group, randomized, double-blind controlled study, conducted between May 2019 and February 2021 compared the change in migraine days per 28 weeks at the end of a 24 weeks treatment period in chronic migraine patients treated with topiramate 100 mg/day ( n = 46) or propranolol ( n = 49) [ 46 ]. The reduction in migraine days per month was -5.3 ± 1.2 days within patients treated with topiramate, and − 7.3 ± 1.1 days within patients treated with propranolol, albeit differences were not statistically significant [ 46 ]. In the case of amitriptyline, a parallel group, randomized, double-blind, double dummy study compared topiramate 100 mg/day ( n = 172) versus amitriptyline 25 mg/day ( n = 159), between patients with 3–12 migraine days per month, with no statistically significant differences in the reduction in the number of monthly migraine episodes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damit wird bei Patienten mit cM vom Gemeinsamen Bundesausschuss (GBA) eine Therapie mit Betablockern, Flunarizin oder Amitriptylin gefordert, deren Wirksamkeit bei der cM nie belegt wurde. Hier gibt es lediglich für Propranolol (160 mg/Tag) erste Daten, dass die Therapieeffekte auf MMD und Alltagsfähigkeit bei Patienten mit chronischer Migräne vergleichbar mit Topiramat (100 mg/Tag) sind [47].…”
Section: Praxisfragen Zum Beenden Einer Medikamentösen Migräneprophylaxeunclassified
“…Several open-label studies have also shown a benefit of combining onabotulinumtoxinA with mAbs to CGRP for CM [192][193][194]. A recent head-to-head trial for chronic migraine showed non-inferiority between propranolol and topiramate, with no significant difference in adverse events incidence between the two [195]. Another prospective randomized trial in chronic migraine compared flunarizine 10 mg with topiramate 50 mg daily, showing both drugs had a similar safety profile, with flunarizine being overall more effective [196].…”
Section: Preventive Treatmentsmentioning
confidence: 99%